Checklist of the helminth parasites of vertebrates in Costa Rica - Beatriz Rodríguez-Ortíz; Luis García-Prieto; Gerardo Pérez-Ponce de León (Revista de Biología Tropical, 2004)
Helminth parasites of vertebrates have been studied in Costa Rica for more than 50 years. Survey work on this group of parasites is far from complete. We assembled a database with all the records of helminth parasites of wild and domestic vertebrates in Costa Rica. Information was obtained from different sources such as literature search (all published accounts) and parasite collections. Here we present a checklist with a parasite-host list as well as a host-parasite list. Up to now, 303 species have been recorded, including 81 species of digeneans, 23 monogeneans, 63 cestodes, 12 acanthocephalans, and 124 nematodes. In total, 108 species of vertebrates have been studied for helminths in Costa Rica (31 species of fishes, 7 amphibians, 14 reptiles, 20 birds, and 36 mammals). This represents only 3.8% of the vertebrate fauna of Costa Rica since about 2,855 species of vertebrates occur in the country. Interestingly, 58 species (19.1 %) were recorded as new species from Costa Rica and most of them are endemic to particular regions. Considering the valuable information that parasites provide because it is synergistic with all the information about the natural history of the hosts, helminth parasites of vertebrates in Costa Rica should be considered within any initiatives to accomplish the national inventory of biological resources. Starting with this compilation work, the Colección de Helmintos de Costa Rica (CHCR), hosted at the Facultad de Microbiología, Universidad de Costa Rica, has reemerged and it is our hope that it will have the standards of quality to assure that it will become the national depository of helminths in the country